A bifunctional carbon catalyst with Cl and SO3H groups for hydrolyzing furfural residue to levulinic acid. Issue 10 (30th June 2022) - Zhang, Shuaibin; Yan, Bochao; Chen, Zhihui; Zhang, Suping
Abstract: BACKGROUND: Levulinic acid, an important platform compound, is extensively used in textiles, dyes, antifreeze, animal feed, solvents and food additives. However, the use of lignocellulosic biomass to produce levulinic acid is difficult because of poor accessibility to cellulose and low hydrolytic yield. Thus a viable hydrolysis strategy and a suitable catalyst must be developed. RESULTS: In this study, a bifunctional solid acid catalyst (HTC‐SO3 H) containing both cellulose binding sites (Cl, COOH and OH) and catalytic sites (SO3 H) was prepared by a carbonization–grafting–oxidization method. X‐ray photoelectron spectroscopy and Fourier transform infrared characterization confirmed the existence of Cl and the successful modification of the SO3 H grafted hydrothermal carbon. The hydrogen bonds formed between cellulose and the binding sites (Cl, OH and COOH) in the catalyst showed synergistic effects with the catalytic sites (SO3 H), leading to efficient hydrolysis of the furfural residue. A total of 74.81% (non‐magnetic) and 70.18% (magnetic) levulinic acid yields were obtained after hydrolysis at 190 °C and 180 min in γ‐valerolactone–H2 O (1:1, v/v). Magnetic catalysts were synthesized using a co‐precipitation method. Catalysts were recycled without any obvious reduction in catalytic activity. CONCLUSION: Using sucralose as a raw material, the as‐synthesized bifunctional solid acid catalyst improved the accessibility to cellulose and increased levulinic acid yield. Moreover, the grafted SO3 H formed by hydroxyl hydration condensation exhibited superior stability. This study provides a valuable strategy for the efficient hydrolysis of lignocellulosic biomass. © 2022 Society of Chemical Industry (SCI).